2015
DOI: 10.1038/ja.2014.169
|View full text |Cite
|
Sign up to set email alerts
|

Natural lipopeptide antibiotic tripropeptin C revitalizes and synergistically potentiates the activity of beta-lactams against methicillin-resistant Staphylococcus aureus

Abstract: Tripropeptin C (TPPC) is a natural calcium-ion-dependent lipopeptide antibiotic that inhibits peptidoglycan biosynthesis by binding to prenyl pyrophosphate. It displays very potent antimicrobial activity both in vitro and in a mouse model of methicillin-resistant Staphylococcus aureus (MRSA) septicemia. The combination of TPPC with all classes of beta-lactams tested (including penam, carbapenem, cephem and oxacephem) showed highly synergistic (SYN) effects against MRSA strains, but not against methicillin-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…More specifically, TPPC forms a complex with undecaprenyl pyrophosphate in the presence of calcium ions and, thus interfering with the lipid cycle of the cell wall synthesis ( Hashizume et al, 2011 ). It has also been reported that TPPC is able to potentiate and re-sensitise MRSA to beta (β)-lactam antibiotics, further indicating this compound’s promise as an effective antimicrobial agent ( Hashizume et al, 2015 ).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…More specifically, TPPC forms a complex with undecaprenyl pyrophosphate in the presence of calcium ions and, thus interfering with the lipid cycle of the cell wall synthesis ( Hashizume et al, 2011 ). It has also been reported that TPPC is able to potentiate and re-sensitise MRSA to beta (β)-lactam antibiotics, further indicating this compound’s promise as an effective antimicrobial agent ( Hashizume et al, 2015 ).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Tripropeptins from Lysobacter sp. strain BMK333-48F3 are another group of cyclic lipodepsipeptides that inhibit the lipid cycle of bacterial cell wall biosynthesis by forming a complex with Ca 2ϩ and undecaprenyl pyrophosphate (11,12). Cephabacins from Lysobacter lactamgenus contain a cephem core attached to an oligopeptide side chain (13)(14)(15).…”
Section: Importancementioning
confidence: 99%
“…133 Notably, tripropeptin C not only has potent antibiotic activity but also is able to reverse β-lactam antibiotic resistance in MRSA. 134 The cyclic lipodepsipeptide is able to revitalize and synergistically potentiate the activity of beta-lactams against MRSA. The mechanism of the reversal is tripropeptin C's inhibition of expression of the β-lactam-inducible blaZ and mecA genes, which encode β-lactamase and foreign penicillin-binding protein, respectively.…”
Section: Natural Products From Lysobactermentioning
confidence: 99%